Antioxidative system in sweet potato root is activated by low‐temperature storage. (16th February 2019) - Wang, Si‐Qi; Tang, Jun; Hu, Kang‐Di; Huang, Zhong‐Qin; Yang, Feng; Zhang, Hui‐Yun; Hu, Lan‐Ying; Li, Yan‐Hong; Yao, Gai‐Fang; Zhang, Hua
Abstract: BACKGROUND: Sweet potato is susceptible to chilling injury during low‐temperature storage. To explore the correlation between chilling injury and reactive oxygen species (ROS) metabolism, the content of ROS and the activities and gene expression of antioxidant enzymes were analyzed in the typical storage‐tolerant cultivar Xushu 32 and storage‐sensitive cultivar Yanshu 25. RESULTS: The activities of antioxidant enzymes including ascorbate peroxidase (APX), superoxide dismutase (SOD), catalase (CAT) and glutathione reductase (GR) were enhanced rapidly in the early period of storage in response to chilling stress. Thereafter, the content of ROS metabolites increased consistently due to gradual decrease in ROS scavenging enzymes. Storage‐tolerant cultivar Xushu 32 had higher antioxidant enzyme activities and gene expressions as well as higher content of antioxidant metabolites and lower content of ROS metabolites compared with storage‐sensitive cultivar Yanshu 25, suggesting that the capacity of ROS scavenging by antioxidant enzymes and antioxidants is highly associated with the tolerance of sweet potato to chilling stress. CONCLUSION: These results indicated that the antioxidative system is activated in the storage root of sweet potato and the antioxidative capacity is positively associated with better storage performance in the storage‐tolerant cultivar. © 2019 Society of Chemical Industry